IMF and the Force of History : Events and Ideas That Have Shaped the Global Institution - Boughton, James (Pamphlet Series; Pamphlet Series, No., 2014)
The world and the IMF have undergone profound changes since the Bretton Woods Conference. James Boughton, former historian of the IMF, looks at key events that have shaped the IMF and the international scene. From the Paris Peace Conference in 1919 to the Great Recession, this essay focuses on 11 events in history that have influenced the design and work of the IMF, as well as the international monetary system. This booklet, prepared for the 70th anniversary of the IMF, is an excerpt from a longer essay that is available on the IMF eLibrary. It is an excellent primer on the motivation behind the founding of the IMF and the evolution of the organization.